Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1002/ijc.2910450520
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of gastric cancer and diet in Italy: II. Association with nutrients

Abstract: A case-control study involving interviews with 1,016 gastric cancer (GC) patients and 1,159 population-based controls in high- and low-risk areas was conducted to evaluate dietary factors and their contribution to the marked geographic variation in mortality from this cancer within Italy. Risks of GC were found to vary significantly with estimated nutrient intake. Risk rose with increasing consumption of nitrites and protein, and decreased in proportion to intake of ascorbic acid, beta-carotene, alpha-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0
9

Year Published

1991
1991
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(113 citation statements)
references
References 25 publications
9
95
0
9
Order By: Relevance
“…[35][36][37] However, a vegetable and fruit diet exerts a protective influence against this disease. 38 Therefore, not everyone infected with pathogenic strains is expected to develop this condition.…”
Section: Association Between H Pylori Infection and Diseasementioning
confidence: 99%
“…[35][36][37] However, a vegetable and fruit diet exerts a protective influence against this disease. 38 Therefore, not everyone infected with pathogenic strains is expected to develop this condition.…”
Section: Association Between H Pylori Infection and Diseasementioning
confidence: 99%
“…Several case -control studies have shown strong inverse associations between GC risk and higher consumption of some of these nutrients (Buiatti et al, 1990(Buiatti et al, , 1991Gonzalez et al, 1994;Hansson et al, 1994;Ekstrom et al, 2000). Results from prospective dietary studies are conflicting and show either a strong protection (Zheng et al, 1995) or no clear inverse associations between the dietary intake of carotenoids and GC risk (Ocke et al, 1995;Botterweck et al, 2000b).…”
mentioning
confidence: 99%
“…Refrigeration may have played a role in reducing gastric cancer rates over the last 60 years by decreasing reliance on food-preservation methods such as salt curing, pickling, and meat smoking (the latter 2 are sources of carcinogenic N-nitroso compounds). 64,65 Cigarette smoking also has been associated with an increased risk of gastric cancer; however, the absence of control for confounders such as H. pylori infection and fresh produce consumption have hindered the interpretation of many studies. [66][67][68] Obesity may be an important risk factor for gastric cancer of the cardia.…”
Section: Discussionmentioning
confidence: 99%